Waxy endosperm corn in growing and finishing rations for swine - B A Koch; G L Allee; Robert H Hines (Kansas Agricultural Experiment Station Research Reports, 1974)
Pigs fed rations containing waxy endosperm corn and those fed normal corn responded similarly in digestion and growing trials. Likewise, finishing pigs responded similarly when fed the two corns in digestion and growing trials.; Swine Day, Manhattan, KS, November 14, 1974
Keywords: Swine day; 1974; Kansas Agricultural Experiment Station contribution; no. 483; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 221; Swine; Waxy endosperm corn; Finishing pigs